The Correlation between Self-Consciousness and Depression in Adolescents - Cazella, Kimberly; Poole, Morgan; Urban, Miranda (Kansas State University. K-State Libraries, 2021)
The purpose of this research proposal is to study the relationship between high levels of self-consciousness and depression among adolescents. In the context of this study, a positive relationship between the study variables is expected to reflect that adolescents are more at risk for the development or continuation of depression or depression symptoms when they experience or maintain high levels of self-consciousness. To assess adolescents’ levels of self-consciousness and severity of depression, participants in this study will be expected to complete a survey questionnaire. The use of these instruments incorporates quantitative data as numerically ranked measurements of personal reflection within a reliable screening. The Revised Self-Consciousness Scale (SCS-R) and the Patient Health Questionnaire (PHQ-9) will be in a combined survey distributed to 100 adolescents aged 9-12 years old. Data will remain anonymous and be collected through a classroom setting. The results of this study are expected to help health professionals, parents, educators, and individuals consider self-consciousness as a more emphasized and prevalent element in adolescent depression and mental health.
Kirmser Undergraduate Research Award - Individual Non-Freshman category, honorable mention
Keywords: Self-Consciousness; Revised Self-Consciousness Scale (SCS-R); Patient Health Questionnaire (PHQ-9); Adolescents; Depression